THE FORMING OF CREATIVE PERSONALITY OF FUTURE MUSIC TEACHER DURING THE INDIVIDUAL HOURS (Pedagogy of Higher and Secondary Education, 2022)
The author view! the necessity of reorientation of individual work and turn if from the informative function to personality, to the forming of students personal creative component.
Keywords: creation; creative personality; teacher of music; the process of individual hours; creative capabilities